Assessment of carbohydrate count and standard diabetic diet on children growth with type 1 diabetes - Pendhari, Ayesha T.; Reddy, Sudha Vardapura Ramalinga; Reddy, M. Madhavi; Bantawal, Ganapathi; Kumar, K. M. Prasanna; Reddy, Sanjay; Kannan, Subramanian (International Journal of Research in Medical Sciences, 2025)
Background: The management of optimal blood glucose levels in type 1 diabetes children is essential with proper nutrition therapy to achieve age-appropriate growth and development and to avoid acute and chronic complications. Methods: One hundred type 1 diabetes aged between 6 and 18 years were on insulin with the duration of one year were enrolled in the study. The participants were divided into two groups of fifty in each. The control group received a standard diet and routine treatment and intervention group received carbohydrate-count diet in addition to standard care. Detailed history, anthropometric, biochemical, clinical examination and 3-day dietary intake were collected at baseline baseline, three months, and after six months. Results: The intervention group exhibited significantly lower mean HbA1c levels than control group, indicating improved glycemic control. Categorizing patients into weight-for-age categories revealed a significant difference in distribution between control group at baseline (CG-38.6±11.9) and after six months (40.4±11.5), p=00024. In comparison, the intervention group showed a significant difference at baseline (IG-37.1±13.6) and after six months (39.4±13.6), p=00001. However, the intervention group showed more substantial improvement in weight gain. Although mean differences in BMI-SDS between control and intervention groups were observed. Conclusions: Carbohydrate counting method showed significant improvement in glycemic levels in intervention group and intern reduced insulin requirement this could achieve the age-appropriate growth patterns in children with Type 1 diabetes.